Cellular Reaction in the Footpad and Draining Lymph Nodes of Mice Induced by Mycobacterial Fractions and BCG Bacilli - Bekierkunst, A. (1971)
Ten micrograms of trehalose-6, 6′-dimycolate (cord factor), injected into the footpad of mice, induced histological changes similar to those following injection of living BCG bacilli. Both materials induced in the draining lymph nodes the formation of granulomas composed of epitheloid cells, macrophages, and small numbers of lymphocytes. Apart from the granulomatous inflammatory process, marked hyperplasia of the lymphoid tissue in the paracortical zone of the nodes and accumulations of macrophages were evident. In some cases, the macrophages were very numerous and replaced part of the lymphoid tissue. Compared to cord factor, wax D showed weak granulomagenic activity. Only slight and transient inflammation was found in the footpads as well as transient slight lymphoid hyperplasia. Wax D also induced small accumulations of macrophages. Complete Freund's adjuvant induced, under the same experimental conditions, large accumulations of macrophages in the draining lymphnode and lymphoid hyperplasia in the paracortical zone. No cellular reaction was seen in the liver, spleen, and lungs after injection of cord factor and BCG into the footpads of the animals. The results and implications are discussed.